PERAN GURU MATA PELAJARAN AL-QUR'AN HADITS DALAM MENGATASI KESULITAN MEMBACA AL-QUR'AN PADA SISWA MADRASAH TSANAWIYAH - Amak Fadholi; Nasrodin Nasrodin; Nila Auliya (MUMTAZ : Jurnal Pendidikan Agama Islam, 2022)
This research is based on the existence of students who have difficulty in pronouncing letter sounds, understanding cursive letters, recognizing long signs, punctuation marks, and practicing the law of reciting recitation. This study aims to determine the role of the Al-Qur'an Hadith subject teacher in overcoming difficulties in reading the Qur'an. the researcher hopes that the teacher is able to overcome these difficulties as a form of effort in eradicating Al-Qur'an illiteracy. The research uses a qualitative approach, therefore the presence of the researcher is a key instrument. The research subjects included teachers of the Al-Quran Hadith subject, and students of primary data and documents as supporting data. Data collection was carried out through observation, interviews and documentation, then the data were analyzed through data reduction, data presentation, and verification, and the validity was checked using source triangulation. The results of this study indicate that the role of the Al-Qur'an Hadith subject teacher in overcoming student learning difficulties is carried out through 1) the role of the teacher as an educator includes: providing exemplary, guidance, direction, and coaching during class hours and outside class hours on how to read al a good and correct Qur'an, 2) as a teacher including teaching material, forming study groups, selecting methods, providing awareness, direction, understanding and motivation on how important it is to read the Qur'an, 3) as a trainer it is done through a group tadarus al Qur'an 'an, facilitating private reading of the Qur'an and training students how to learn the Qur'an in a good and correct way.